Determination of serum brassicasterol in spontaneously hypertensive rats stroke‐prone fed a high‐ergosterol diet by ultra performance liquid chromatography. Issue 7 (13th October 2015) - Ohtsubo, Takaaki; Kageyama, Ryo; Koseki, Yuji; Hagi, Junya; Kotani, Akira; Yamamoto, Kazuhiro; Kusu, Fumiyo; Miura, Tsuyoshi; Hakamata, Hideki
Abstract : A method for the determination of ergosterol, brassicasterol, and cholesterol has been developed by ultra performance liquid chromatography with ultraviolet detection (UPLC‐UV). Using an ODS column and a mobile phase of acetonitrile‐water (95:5, v/v), we found that the peak area was linearly related to the amount of sterols injected, ranging from 1.5 to 100 μmol/L ( r  ≥ 0.998), except for cholesterol (2.5–400 μmol/L). Repeated injection showed that the relative standard deviation (RSD) at 50 μmol/L of sterols was less than 7.1% (intra‐day, n  = 6) and 13% (inter‐day, n  = 3). Ergosterol and brassicasterol in rat serum spiked at four concentration levels (16, 25, 100, 250 μmol/L) was determined by the internal standard (IS) method using campesterol as an IS with the recovery of more than 88.8% and the RSD ( n  = 5) of less than 12.5%. Practical applications : This method has been applied to determine the serum ergosterol and brassicasterol concentration in spontaneously hypertensive rats stroke‐prone (SHRSP rats) fed a high‐ergosterol diet containing 1% ergosterol. The results indicate that no apparent peak for ergosterol was observed, whereas the serum brassicasterol concentration was increased by the ergosterol‐feeding. Brassicasterol was confirmed by electrospray ionization triple quadrupole tandem mass spectrometry after derivatization to picolinyl esters. In addition, brassicasterol‐ d 1 was detected after oral administration of ergosterol‐ d 1 to SHRSP rats by ion‐trap time‐of‐flight mass spectrometry. Because SHRSP rats are known as an experimental animal model of phytosterolemia, it has been expected that ergosterol is absorbed and converted to brassicasterol. In summary, the current method provides an experimental tool to help understand ergosterol absorption and metabolism. A method for the determination of ergosterol, brassicasterol, and cholesterol has been developed by UPLC‐UV. We found that a high‐ergosterol diet induces the elevation of serum brassicasterol in SHRSP rats. Abstract : A method for the determination of ergosterol, brassicasterol, and cholesterol has been developed by UPLC‐UV. We found that a high‐ergosterol diet induces the elevation of serum brassicasterol in SHRSP rats.